Development of microsatellite markers for Anadenanthera colubrina var. cebil (Fabaceae), a native tree from South America - Barrandeguy, Maria Eugenia (2012)
•Premise of the study: Microsatellite primers were developed in the native legume tree Anadenanthera colubrina var. cebil to study the genetic diversity and genetic structure in natural populations in Argentina. •Methods and Results: Nine microsatellite markers were identified using a genomic library enriched for tandemly repeated motifs, eight of which markers were polymorphic. The polymorphism of these markers was assessed by investigating 20 individuals for fragment polymorphism; three to 13 alleles were observed for each locus. Observed and expected heterozygosities ranged from 0.300 to 1.000 and from 0.463 to 0.900, respectively. • Conclusions: These results confirm that these primers will be useful for investigating the genetic diversity and genetic structure of natural populations of A. colubrina var. cebil in future studies.